METHODS OF PROSECUTOR’S SUPERVISION OF COMPLIANCE WITH LAWS TO ENSURE THE RIGHTS OF THE SUSPECT - Bugayov, Yaroslav (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2021)
Introduction. According to Article 3 of the Constitution of Ukraine, a person, his life and health, honor and dignity, inviolability and security are recognized as the highest social value. Human and civil rights and freedoms and their guarantees determine the content and direction of the state. The functioning of the constitutional legal mechanism to ensure the fundamental rights and freedoms of participants in criminal proceedings is determined by the task of effectively ensuring the rights and freedoms of everyone from abuse and arbitrariness by operational units, investigators, investigators by prosecutorial response based on procedural control, state bodies and their officials. Summary of the main research results. The article considers the methods of prosecutorial control over the procedural activities of the investigator, provides legal constructions for improving the methods and techniques of control. Methods of prosecutorial control should include the basic provisions of legality, reasonableness, completeness of the pre-trial investigation, establishing the guilt of the suspect and the circumstances of the criminal offense. The method of prosecutorial activity can be determined, which is a set of theoretically substantiated and empirically confirmed methods of performance by the prosecutor of the function of prosecution, establishing the circumstances of a criminal offense. Conclusions. The article offers theoretical aspects and practical solutions to emerging problems on the basis of the criminal process of Ukraine. The method of prosecutorial control and supervision in criminal proceedings includes the optimal methods and means of exercising the powers of the prosecutor at the stage of pre-trial investigation.